Reducing health provider stereotypes through undergraduate interprofessional education - Kerry, Wilbur (2022)
ObjectiveStereotypes among health professionals can jeopardize the delivery of collaborative healthcare and the achievement of positive patient outcomes. However, interprofessional education (IPE) can promote early clarification of roles, and understanding and mutual respect among trainees from different health disciplines. We studied the effects of IPE activities on the views and attitudes of pharmacy students toward nurse- and physician-trainees. MethodsPharmacy students completed a structured written reflection exercise immediately following two separate IPE activities with nursing and medical students, both oriented around diabetes care. We conducted an inductive content analysis of these texts to identify key themes according to the domains of the contact hypothesis theoretical framework: organizational authority, common goals, intergroup cooperation, equal group status and intergroup status. Pharmacy students were also asked how these IPE activities have influenced their views regarding their future pharmacy practice. ResultsPharmacy students felt that their groups had cooperated to solve the common patient care goals in each IPE activity, and noted no distinction between the nursing and medical students. However, through either explicit or implicit negotiation of overlapping roles, many pharmacy students ultimately assumed deferential positions relative to medical students. Overall, pharmacy students' attitudes and views regarding the abilities and roles of nursing and medical students in patient care were favorably altered through the IPE activities. Notably, nurses' drug knowledge and diagnostic abilities of nurses and physicians’ familiarity with the primary literature and prescribing regimens was previously under-rated but became recognized after IPE activities. ConclusionPharmacy students’ stereotypical views towards nursing and medical students were positively shifted when IPE activity conditions were optimized for intergroup contact.